Tipificación del fraude deportivo como un tipo penal en Ecuador - Rengifo Aispur, Jeanpierre Ivan (2025)
This research addresses the issue of sports fraud, because in Ecuador it can be evidenced how there are behaviors aimed at altering, falsifying or rigging sporting events that are not considered a crime. Thus, the objective of the scientific article is to elaborate a document of critical legal analysis through which it is possible to justify the affectation of the right to property by not typifying sports fraud as a criminal offense. In order to understand and solve the phenomenon, the research work has a qualitative methodology, using methods such as analytical-synthetic, inductive-deductive, exegetical and comparative law, since it is through these methods, together with the other methods, The results that are reached address how this crime is typified in Spain and Portugal punctually, and the legal good that is protected by this crime in these legislations, with which finally we can reach the conclusions of the research, where it is justified that this crime should indeed be typified in the Ecuadorian Organic Integral Penal Code.